CAUSES FOR CONCERN: IS NICE FAILING TO UPHOLD ITS RESPONSIBILITIES TO ALL NHS PATIENTS?. (January 2015) - Claxton, Karl; Sculpher, Mark; Palmer, Stephen; Culyer, Anthony J
ABSTRACT Organisations across diverse health care systems making decisions about the funding of new medical technologies face extensive stakeholder and political pressures. As a consequence, there is quite understandable pressure to take account of other attributes of benefit and to fund technologies, even when the opportunity costs are likely exceed the benefits they offer. Recent evidence suggests that NICE technology appraisal is already approving drugs where more health is likely to be lost than gained. Also, NICE recently proposed increasing the upper bound of the cost‐effectiveness threshold to reflect other attributes of benefit but without a proper assessment of the type of benefits that are expected to be displaced. It appears that NICE has taken a direction of travel, which means that more harm than good is being, and will continue to be, done, but it is unidentified NHS patients who bear the real opportunity costs. Copyright © 2014 John Wiley & Sons, Ltd.